2020
DOI: 10.1097/bpb.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pediatric distal femoral physeal fractures and the factors impacting poor outcome requiring further corrective surgery

Abstract: Fractures of the distal femur carry a significant risk of physeal arrest and resulting growth complications which often require additional surgeries to correct the deformity. This study examines the risk of needing corrective procedures as a child approaches skeletal maturity. A retrospective analysis of patients treated at a single institution for distal femoral physeal fractures from 2000 to 2015 was performed. Association between sex, age, Salter–Harris (SH) class, and fracture displacement with the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…When compared to other subtypes of SH fractures, type I fractures were associated with the lowest risk of growth disturbances in a meta-analysis of 564 fractures [ 2 ]. Bellamy et al concluded that the severity of fracture displacement and remaining years of growth until skeletal maturity was associated with an increased risk of requiring corrective surgery for growth disturbance [ 10 ]. In addition to fracture displacement, Arkader et al stated that the severity of fracture according to SH classification was significantly correlated with the incidence of growth disturbance [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to other subtypes of SH fractures, type I fractures were associated with the lowest risk of growth disturbances in a meta-analysis of 564 fractures [ 2 ]. Bellamy et al concluded that the severity of fracture displacement and remaining years of growth until skeletal maturity was associated with an increased risk of requiring corrective surgery for growth disturbance [ 10 ]. In addition to fracture displacement, Arkader et al stated that the severity of fracture according to SH classification was significantly correlated with the incidence of growth disturbance [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although SH Type II fracture is the most commonly reported physeal fracture, SH type IV fracture seems to have the worst impact on bone growth demonstrated by having the highest incidence of growth rate disturbance compared to other SH fracture types. Overall, more than one-fifth of the growth plate fracture occurring on distal femurs exhibited leg length discrepancy of more than 1.5 cm as a sequela, reported from pooled data [1] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 98%
“…Out of the five possible types in the classification, distal femoral physeal fractures are commonly seen with SH type II fractures, not excluding possibilities of other fracture types occurring. Complications that may arise are hindered growth, irreversible decrease in range of motion, and angular deformity [1] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In multivariable analysis, dislocation exceeding 10 mm was a risk factor for PPC (OR 6.3, CI 1. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Mechanism of injury often involves highenergy trauma, with the most common injury mechanisms being motor vehicle accidents (MVA), sports-related accidents, and falls [4][5][6]. The fractures exhibit exceptionally high complication rates, most commonly premature physeal closure (PPC), which has been reported to occur in up to 21-35% of patients [4][5][6][7][8].…”
mentioning
confidence: 99%